Pelanggaran Lalu Lintas oleh Rombongan Pengantar Jenazah di Jeneponto Perspektif Hukum Islam dan Hukum Pidana - Muhammad Syarwan Syarif; Marilang Marilang (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
The main problem of this of this reseach is traffic violations by the corpse delivery group in Jeneponto, the perspective of Islamic law and criminal law. The main problem is then formulated into several sub problems, namely 1.) what are the forms of violations by the group delivering the corps? 2.) how does the positive law view traffic violations by the group delivering the bodies? 3.) how does Islamic law view violations during delivery of the corpse? This type of reseach is classified as field reseach, with a reseach approach using a sociology of law approach. As for the reseach data sources are the public and law enforces in Jeneponto district. This study aims to determine the forms of violations, as well as the elaboration of rules related to community habits, in this case the delivery of corpses, through the perspective of Islamic law and positive law (case study of the corpse delivery group in Jeneponto district). This type of reseach is quantitative reseach, which is a method that emphasizes the understanding of social problems based on (real) and natural conditions of reality. The focus of this reseach will emphasizes on data analysis and basic analysis of control, as well as providing articles to traffic offenders in transporting their bodies. Data collection methods and drawing conclusions as well as documentation. This reseach is considered impostant because of the many violations that occur when delivering the corpse, and it cannot be separated from adding a wealth of thoughts and insights for the author himself and the reader later.Keywords: violaton, introduction to the body, Islamic law, criminal law.